Exploring Consumer’s Expectations and Perceptions of Brands During the Coronavirus Contingency - Teresa Treviño Benavides; Flor Morton Rodríguez (Ciencias Administrativas Teoría y Praxis, 2022)
In the midst of a vast spread of COVID-19 across the world, legal regulations were introduced in most countries including social distancing, travel restrictions, and a lockdown in an attempt to slow down the spread of the virus. The pandemic caused by COVID-19 has raised companies’ awareness of the need to foster consumer’s trust in order to survive a crisis. Therefore, the present paper aims to understand the expectations that consumers have towards the behaviors and strategies implemented by brands during the pandemic. This paper contributes to the discussion on how consumers perceive brand’s reactions to the pandemic, by showing ways in which brands can foster brand trust through manifestations of competence, problem-solving and benevolence/integrity. Following an exploratory qualitative research, findings of interviews with consumers suggest that they are informed and interested in brands' efforts towards the topic, and in fact the brand’s positive or negative reactions to the pandemic can shape brand trust.